Are we over-estimating irrigation subsidies in multipurpose water resources projects in India? methodological issues and evidence - Kuppannan, Palanisami; Malik, Ravinder Paul Singh; Mohan, Kadiri (2012)
Irrigation subsidies have become a highly contentious issue over the years and alternative approaches and conventions have been evolved in measuring the magnitude of these subsidies. Given the fact that the capital cost is a sunk cost, this paper has used the O&M cost of the project and the gross receipts in computing irrigation subsidies. Further, the paper has suggested an improvement in the subsidy estimation methods by adjusting the O&M cost of the projects to multiple benefits of the irrigation projects using the Separable Cost Remaining Benefit (SCRB) method in three major multipurpose irrigation projects in the state of Andhra Pradesh. The study has revealed that currently irrigation subsidies are over-estimated. For example, the estimated average irrigation subsidy in Nagarjunasagar Project (NRSP) Right Bank canal based on currently practised methods, works out to be ` 428 per ha, whereas using the SCRB approach, it come to be ` 111/ ha. The irrigation subsidy for NRSP is thus being currently over-estimated to the tune of almost 286 per cent. Similar is the case with the other two projects studied, though the magnitude of subsidy over-estimation could differ. The study has demonstrated how through the use of appropriate accounting methodologies, more informed and transparent estimates of irrigation subsidy can be derived. The inference from this paper is that reliable information about subsidies actually going to the irrigation sector could help in framing better pricing policies for irrigation water and in promoting more efficient use of irrigation water and utilization of subsidies. The outcome from the study will also be useful in finetuning the subsidy related discussions in the 12th Five-Year Plan documents.